Design of an Artificial Intelligence Based Recommendation System to Improve User Experience On E-Commerce Platforms - Afrizal Zein (Journal of Science Technology (JoSTec), 2024)
The objective of this research is to explore the design and development of an artificial intelligence-based recommendation system to enhance user experience on e-commerce platforms. The research methodology employed is qualitative research, a method used to gain in-depth understanding of social phenomena. The chosen type of research is a literature review, where in the researcher collects, studies, and analyzes written references or sources such as books, journals, articles, documents, and other significant sources of information related to the researched topic or title. Subsequently, the researcher analyzes and draws conclusions to find answers to the research questions. The research findings indicate that the development of an artificial intelligence-based recommendation system for improving user experience on e-commerce platforms is a relevant and pressing step. By comprehending various aspects discussed in the literature, the researcher can design a system that is not only accurate and efficient but also ethical, secure, and aligned with user needs. For future researchers, further studies are needed, and practical implementation steps will be crucial to translate literature findings into tangible solutions that can enhance the e-commerce landscape in the future.